Bio-Methanation of Anaerobic Fermentation of Undiluted Cattle Dung - Vani, D K; Kurchania, A K (Journal of Agricultural Engineering, 2007)
Non-availability of sufficient water required for necessary dilution of input slurry for biogas plants is considered to be the major hurdle in popularization of technology. The problem can be solved through biomethanation of undiluted cattle dung. Experimentation with undiluted cattle waste through anaerobic fermentation showed good results. Along with substrate ’"A" i.e. undiluted cattle dung, two substrates namely, "B" (prepared by adding water equal to half of the weight of cattle dung and 9% active inoculum) and "c" (prepared by mixing cattle dung with equal weight of water and 6% active inoculum) were experimented. Total biogas production from 3 kg substrate in 5.3 litre capacity glass bottle fermenters in 80 days were recorded as 130.7, 113.5 and 85.5 litre for substrate A, Band C, respectively. Biodegradability was found as 50.5, 58 and 59% for substrate A, B and C, respectively. Results revealed that the solid-state fermentation for longer hydraulic retention time (80 days) is comparable with the traditional practices of biogas production.